Water mining and landscape: study on north-western part of Bankura district, west Bengal, India - Bhutia, Namgyal Tshewang; Sinha, Malavika (Acta Geographica Debrecina Landscape & Environment series, 2022)
Groundwater depletion occurs when the rate of groundwater extraction is higher than the rate of replenishment. It is unequivocal that the demand for fresh water is ever increasing. The study area lies in the semi-arid climatic zone and it’s a solely agrarian society. The water scarcity leads to an impact on soil moisture and soil becomes drier during the dry months. The study is based on the changes in the regional water table which exhibit a relatively rapid response to acute scarcity of water. To specify the soil dryness gravimetric method has been used to study the selected soil samples. The groundwater withdrawal without estimating the water requirement at the regional level leads to soil dryness, and water stress situation to the agrarian economy, and it leaves a direct impact on the land. The perception of the farm owner, that ownership of farmland is synonymous with water mining right from their land leads to stress on the water table.